Humour and Irony in Dutch Post-war Fiction Film - Verstraten, Peter (Amsterdam University Press, 2016)
If Dutch cinema is examined in academic studies, the focus is usually on pre-war films or on documentaries, but the post-war fiction film has been sporadically addressed. Many popular box-office successes have been steeped in jokes on parochial conflicts, vulgar behavior and/or on sexual display, towards which Dutch people have often felt ambivalent. At the same time, something like a 'Hollandse school', a term first coined in the 1980s, has manifested itself more firmly, with the work of Alex van Warmerdam, pervaded in deadpan irony as its biggest eye-catcher. Using seminal theories of humor and irony as an angle, this study scrutinizes a great number of Dutch films on the basis of categories such as low-class comedies; neurotic romances; deliberate camp; cosmic irony, or grotesque satire. Hence, Humour and Irony in Dutch Post-war Fiction Film makes surprising connections between films from various decades: Flodder and New Kids Turbo; Spetters and Simon; Rent a Friend and Ober;